When ‘you’ means ‘I’: the german 2nd ps. sg. pronoun 'du' between genericity and subjectivity - Auer, Peter; Stukenbrock, Anja (Open linguistics, 2018)
In this paper, we first present a close analysis of conversational data, capturing the variety of non-addressee deictic usages of du in contemporary German. From its beginnings, it has been possible to use non-addressee deictic du not only for generic statements, but also for subjective utterances by a speaker who mainly refers to his or her own experiences. We will present some thoughts on the specific inferences leading to this interpretation, making reference to Buhler’s deixis at the phantasm. In the second part of the paper, we show that non-addressee deictic du (‘thou’) as found in present-day German is not an innovation but goes back at least to the 18th century. However, there is some evidence that this usage has been spreading over the last 50 years or so. We will link non-addressee deictic du back historically to the two types of “person-shift” for du discussed by Jakob Grimm in his 1856 article “Uber den Personenwechsel in der Rede” [On person shift in discourse]. Grimm distinguishes between person shift in formulations of “rules and law” on the one hand, and person shift in what he calls “thou-monologue” on the other. The subjective interpretation of non-addressee-deictic du in present-day German may have originated from these “thou-monologues”
Gesehen am 14.02.2022
Im Titel ist "nd" hochgestellt